Rodzaj i poziom wsparcia społecznego a poziom depresji i style radzenia sobie u studentów narodowości polskiej uczelni zagranicznych - Godek, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
This paper is an attempt to answer the question on the role of the social support in the process of coping with stress within a group of Polish students in an acculturative stress situation. The research had two primary goals. The first goal was to show the differences between students of Polish nationality enrolled at foreign universities and students of Polish universities in terms of social support, coping with stress and the depression level. The second goal was to examine relations between those three variables. In order to select groups with high and low social support the scale of social support by Kmiecik-Baran has been used. In order to define styles of coping with stress, preferred by the cured drug addicts, the Polish version of The Coping Inventory for Stressful Situations has been used. Both groups responded to the Beck Depression Inventory (BDI), consisting of a self-evaluated scale of 21 items, each with four assertions corresponding to increasing levels of depressive symptoms. The obtained results indicate that students of Polish universities were characterized by a lower level of social support and they reported higher levels of depression than the control group of Polish students living abroad. The groups did not differ significantly with respect to the measures of coping styles. According to the results of the study, the stronger preference for the emotion-oriented coping style, the higher level of depression, which indicates that this coping style was ineffective in dealing with stressful life events in both groups of students. In addition, the level of received social support was negatively correlated (r = –0,589) with the task-oriented coping style in a group of students in Poland.